Nilai biodiversitas lanskap mangrove DKI Jakarta, Kelurahan Penjaringan, Kecamatan Muara Kamal, Jakarta Utara - Audia Inayah; Kaswanto Kaswanto (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
This research is in the mangrove landscape of DKI Jakarta which is in Penjaringan District, Muara Kamal Village, North Jakarta. The location is close to human activity. Mangrove sampling was carried out at 4 different locations but still in the same area, including: Galatama Fishing Mangrove Ecosystem Area, Elang Laut Block of Mangrove Ecosystem, Muara Angke Wildlife Reserve and Angke Kapuk Mangrove Ecotourism. This study aims to determine the composition and distribution of mangrove vegetation, as well as calculate the index values of diversity index, uniformity index, and dominance. Based on inventory data, many types of Rhizophora mucronate were found at research sites where the sapling level had the highest percentage identified. Diversity index is 0.47 – 1.43, means in the low to medium level. Uniformity index is in the low to high level, namely 0.34 – 0.81. Dominance index is 0.35 - 0.79, means in the low to high level .